PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK IDENTIFIKASI PREFERENSI KONSUMEN PADA PEMILIHAN MINYAK PELUMAS SEPEDA MOTOR TIPE 4-TAK - Bayu Manila; Agung Sutrisno; Johan S.C. Neyland (JURNAL POROS TEKNIK MESIN UNSRAT, 2014)
Lubricating oil available in a wide range which is offered consumers through the promotion in order to convince consumers that the product is the best. This study aims to determine preferences of consumers in the selection of motorcycle 4-stroke type lubricating oils using Analytical Hierarchy Process (AHP) method. From the analysis using the AHP based on criteria, it shows that durability is ranks the first with a weight value of 0.5034, following with stock availability (0.5019), price (0.4248), and recommendations of manufactorer coming last (0.3840). As for the preference of alternative lubricating oil, analysis base on brand of motorcycle it shows that Yamaha with Yamalube 7.5% all criteria, Honda with Yamalube of respective value 4.77% and 4.37% on criteria recomendation of manufactorer and price, Enduro 3.16% the stock availability, and federal 3.08% for durability. Suzuki of Yamalube which is value of 3.43% and 3.05% on criteria recommendation of manufactorer and price, Enduro ​​respectively 3.56% and 3.43% to criteria stock availability and durability. Kawasaki on Enduro with 43.76% and 26.85% to the price and stock availability, Top-1 27.17% and 31.28% to recommendations of manufactorer and durability. Keywords : Preferences, Oil Lubricants, AHP, Criteria